Manufacturing method of E0-grade poplar low-odor fiberboard and fiberboard thereof

By adding antibacterial and anti-mold agents, applying deodorant and environmentally friendly adhesives in the manufacturing process of poplar fiberboard, and carrying out specific process treatments, the odor problem of poplar fiberboard is solved, achieving low odor, anti-bacterial and anti-mold effects, improving the effect of improving The quality and function of the board.

CN119116091AActive Publication Date: 2024-12-13DARE WOOD BASED PANEL GRP

Patent Information

Application Number
CN202411316290.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing poplar fiberboard has irritating odor problems, which mainly comes from microbial corruption during storage, high temperature and high pressure reactions during production, and volatility of additives, which affects its quality and safety in furniture and other fields.

Method used

A method for manufacturing E0 grade poplar low-odor fiberboard, including adding antibacterial and anti-mold agent, applying deodorant and environmentally friendly adhesive, controlling the cooking temperature and time, drying and hot pressing treatment, and using nanotitanium dioxide as deodorant, Degradation of odor molecules by photocatalytic.

Benefits of technology

It effectively reduces the odor molecular concentration of poplar fiberboard, eliminates acidic and oxidized odors of fatty acids, improves the environmental quality and function of the board, meets the needs of high-quality life, and achieves low odor and antibacterial and anti-mold effects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of wood processing, and relates to a manufacturing method of an E0-grade poplar low-odor fiberboard, which comprises the following steps: peeling poplar, chipping, adding an antibacterial and mildew-proof agent, storing for 1-2 months, screening wood chips, washing with water, cooking, separating fibers, and mixing and applying glue. Comprising the following steps: applying a deodorant, an environment-friendly adhesive, a waterproof agent and a curing agent, drying and sorting, paving and forming, pre-pressing, hot-pressing, turning over and cooling, sanding, spraying a sealing agent, inspecting and grading, and packaging and warehousing. According to the E0-grade poplar low-odor fiberboard produced by the method, the acid corrosion odor of an existing poplar board due to parasitic metabolism of microorganisms can be eliminated, the peculiar smell caused by fatty acid oxidation is reduced, the odor of wood is adsorbed, and the odor molecule concentration is reduced. The added titanium dioxide is distributed in the plate, and peculiar smell is continuously eliminated through photocatalysis; the environment-friendly quality and functions of the fiberboard are improved, and the requirements of high-quality life are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood processing, relates to the manufacture of fiberboard, and particularly relates to a manufacturing method of an E0-grade poplar low-odor fiberboard and the fiberboard. Background Art

[0002] my country is the world's largest producer, consumer and trader of wood materials and products, with an annual total output value of more than 3 trillion yuan. As the main wood material, wood-based panels are widely used in furniture and architectural decoration. Fiberboard, one of the important sub-categories of wood-based panels, is a type of board made from wood fiber or other plant fiber, which is prepared by fiber preparation, applied with synthetic resin, and pressed under heating and pressurization conditions. As people's pursuit of a better life continues to improve, consumers in the custom home furnishing industry are paying more and more attention to the smell of furniture. Some existing boards have irritating odor problems. Custom home furnishing hopes that board companies can provide green, environmentally friendly, and low-odor boards for the manufacture of wardrobes, cabinets and other furniture.

[0003] The main sources of odor in fiberboard made from poplar wood are as follows: (1) The decay odor caused by high temperature and high humidity during the storage of poplar and poplar wood chips. This is mainly caused by the parasitism and proliferation of certain microorganisms under suitable temperature and humidity conditions during the storage process, which then metabolize to produce new compounds, emitting the sour and decayed odors of poplar wood; (2) During the production of poplar fiberboard, the high temperature and pressure as well as the appropriate amount of water in the cooking process will cause the dissolution and volatilization of wood extracts. Lipids and oxygen react under the influence of temperature, moisture, and light to produce aldehydes, ketones, acids, and alcohols, thereby producing unpleasant odors; (3) Foreign odors caused by additives applied during the production of boards, such as inappropriate adhesives and waterproofing agents; (4) The odor of poplar itself. The odor of wood itself mainly comes from high molecular weight compounds in wood cells, such as organic compounds such as terpenes. The odor produced by the terpene compounds in fast-growing wood itself is a naturally released compound and is harmless to human health. Summary of the invention

[0004] In order to reduce the odor of poplar fiberboard, it is necessary to eliminate the irritating and unpleasant odors caused by the sourness and aldehydes, ketones, acids, etc. generated during the storage and production process of poplar. The present invention discloses a method for manufacturing an E0-grade poplar low-odor fiberboard to achieve odor reduction and control of the fiberboard, obtain a low-odor fiberboard, provide support for improving the quality of the board, and further expand the application of the fiberboard in interior decoration.

[0005] Technical Solution

[0006] A method for manufacturing an E0-grade poplar low-odor fiberboard, comprising: poplar peeling → chipping, adding antibacterial and mildew-proofing agents → storing for 1 to 2 months → wood chip screening → water washing → steaming → fiber separation → glue preparation, including applying deodorant, environmentally friendly adhesive, waterproofing agent, curing agent → drying and sorting → paving and forming → pre-pressing → hot pressing → board turning and cooling → sanding → spraying sealant → inspection and grading → packaging and warehousing, wherein:

[0007] The chippings, adding an antibacterial and antifungal agent step, adding 0.1-1% of the mass of the dry wood chips, preferably 0.5% of the antibacterial and antifungal agent to the poplar chips;

[0008] The steaming process comprises a pre-cooking temperature of 85 to 90° C., a steaming temperature of 160 to 170° C., and a steaming time of 2 to 2.5 minutes;

[0009] The adhesive preparation includes applying a deodorant, an environmentally friendly adhesive, a waterproofing agent, and a curing agent. The amount of the deodorant added is 1 to 3 kg / m 3 , preferably 2kg / m 3 , the application amount of environmentally friendly adhesive is 175~220kg / m 3 , preferably 200kg / m 3 ; The amount of waterproofing agent added is 4 to 8 kg / m 3 , preferably 6kg / m 3 ; The amount of curing agent added is 2 to 4 kg / m 3 , preferably 3kg / m 3 ; Each component is applied relative to the volume of wood fiber.

[0010] In a preferred disclosed example of the present invention, the mildew and antibacterial agent is a mildew and antibacterial agent of model KEPUYIN-M002 produced by Guangdong Kepuyin Biotechnology Co., Ltd.; when used, 5 to 20 times of water is added to dilute it into a solution.

[0011] In a preferred disclosed embodiment of the present invention, the deodorant is applied to the poplar wood fiber alone, or is mixed with the environmentally friendly adhesive and then applied to the poplar wood fiber at the same time.

[0012] In a preferred disclosed embodiment of the present invention, the main component of the deodorant is nano titanium dioxide.

[0013] Furthermore, the deodorant, its preparation method comprises the following steps:

[0014] A. Weigh a plant extract, wherein the plant extract is one or more of tea polyphenol extract, rosemary extract, licorice extract, and citric acid, wherein the tea polyphenol extract is 0-20 parts, the rosemary extract is 0-10 parts, the licorice extract is 0-10 parts, and the citric acid is 0-2 parts, and each component is not 0 parts; then weigh one or more of the emulsifiers Tween 20T-20, Span 80Span-80, and fatty alcohol polyoxyethylene ether AEO-9, wherein the mass of the emulsifier is 1-3 times that of the plant extract, and mix and stir evenly;

[0015] B. Weigh 1 to 3 times the mass of hydroxypropyl-β-cyclodextrin of the plant extract and dissolve it in deionized water to prepare an aqueous solution with a concentration of 5 to 15%. Slowly pour the hydroxypropyl-β-cyclodextrin solution along the wall into the mixture obtained in step A, and stir to make the solution system uniform.

[0016] C. Adjust the pH value of the system to 5.0-9.0 with sodium hydroxide solution, continue stirring, and after the system is stable, add nano titanium dioxide, continue stirring, and prepare a translucent to white emulsion, that is, the content of the nano titanium dioxide is 1-4wt.% of the finished emulsion.

[0017] According to a preferred disclosed example of the present invention, in step A, the tea polyphenol extract is 10 parts, the rosemary extract is 5 parts, the licorice extract is 5 parts, and the citric acid is 1 part.

[0018] According to a preferred embodiment of the present invention, in step C, the concentration of the sodium hydroxide solution is 0.1 mol / L.

[0019] In a preferred disclosed example of the present invention, in step C, the particle size of the nano titanium dioxide is 10 to 20 nm, and the content is 3 wt.% of the finished emulsion.

[0020] In a preferred disclosed embodiment of the present invention, the preparation process of the environmentally friendly adhesive comprises the following steps:

[0021] (1) Add F1 to the reactor, adjust the pH to 8.5-9.0 with caustic soda solution, add U1, stir, heat to 85°C within 30-40 minutes through steam, keep warm for 13-16 minutes, preferably 15 minutes, and control the pH to 6.5-7.5;

[0022] (2) Slowly adjust the pH to 4.5-4.7 with formic acid and react at 88-89°C until white mist appears when the reaction solution is dropped into ice water;

[0023] (3) adjusting the pH of the reaction solution to 6.0-6.5 with caustic soda solution, adding U2, raising the temperature to 85°C, and keeping the temperature for 8-12 minutes, preferably 10 minutes;

[0024] (4) Adjust the pH to 9.0-9.3 with caustic soda solution, add F2 and M, raise the temperature to 88-92°C, and keep the system at 90°C for 45 minutes. During the constant temperature process, the pH is always kept above 8.3;

[0025] (5) After the constant temperature is finished, cool quickly with cooling water, add U3 at 80°C, cool to 35°C, adjust the pH to 7.0-8.0, and discharge the glue;

[0026] Among them, the amount of melamine (M) accounts for 5-12% of the mass of the environmentally friendly adhesive, the molar ratio of formaldehyde (F) to urea (U) and melamine is 0.80-0.82; formaldehyde is added twice, of which F1 is 84% ​​and F2 is 16%; urea is added three times, and melamine is added once; the molar ratio of F1 to U1 is 2.0-2.2; the molar ratio of F1 to the sum of U1+U2 is 1.4-1.6.

[0027] In a preferred disclosed embodiment of the present invention, the mass percent concentration of the caustic soda solution used for adjusting the pH is 25%.

[0028] In a preferred disclosed embodiment of the present invention, the waterproofing agent is No. 58 fully refined paraffin.

[0029] In a preferred disclosed example of the present invention, the curing agent is a composite curing agent, which is a mixture of phosphoric acid and ammonium sulfate in a molar ratio of 1:1, the concentration of the aqueous solution after the mixture of the two is 20-40%, and the pH value of the aqueous solution is 4-5.

[0030] In a preferred embodiment of the present invention, in the drying and sorting process, the inlet temperature of the drying temperature is 160-180°C, and the outlet temperature is 80-90°C.

[0031] According to a preferred disclosed example of the present invention, in the hot pressing process, the hot pressing temperature is set at 170-235°C, and five temperature zones are adopted; the hot pressing pressure is 0-4MPa, the hot pressing factor is 7.0-8.0s / mm, and the maximum pressure is 3MPa.

[0032] The E0-grade poplar low-odor fiberboard manufactured according to the method of the present invention not only meets all the physical and chemical properties of ordinary fiberboard GB / T11718, but also meets the odor level ≤ level 2 in LY / T3236-2020 "Odor Classification and Evaluation Method of Artificial Boards and Their Products".

[0033] The key points of the method for producing low-odor poplar fiberboard described in the present invention are: selection and application of antibacterial and mildew-proof agents; preparation and application of deodorants; preparation and application of E0-grade adhesives matching the deodorants; appropriate time and temperature for wood chip cooking process, appropriate pressure, temperature and speed for drying process and hot pressing process.

[0034] Poplar wood chips are prone to mold and rot when stored in an environment with suitable temperature and humidity, and microbial fermentation produces a pungent odor. Therefore, it is necessary to add an appropriate amount of antibacterial and mildew preventer during the poplar chipping process.

[0035] Since the semi-fiber content of poplar wood is higher than that of pine and other miscellaneous woods, the water absorption thickness expansion rate of the board will be higher, and some poplar woods have a higher pH. Therefore, the preparation of environmentally friendly adhesives adopts the step of adding formaldehyde twice, so that the reaction of formaldehyde with urea and formaldehyde with triamine is more complete. The first time formaldehyde and urea undergo polycondensation reaction under acidic conditions to generate sufficient methylol groups to ensure the joint strength of the adhesive. The second time formaldehyde and melamine react under alkaline conditions to generate methylol melamine. This group has good water resistance, which can improve the water resistance of the glue and thus improve the water resistance of the poplar board. Add a deodorizer containing titanium dioxide to reduce the odor of the poplar board through photodegradation and scenting.

[0036] Beneficial Effects

[0037] The E0-grade poplar low-odor fiberboard produced by the present invention can eliminate the sour and rancid smell of existing poplar boards caused by the parasitic metabolism of raw materials by microorganisms, reduce the odor caused by fatty acid oxidation, absorb the odor of the wood itself, and reduce the concentration of odor molecules. At the same time, the titanium dioxide added in the formula is distributed in the board, and the odor is continuously eliminated through photocatalysis. During the subsequent storage and use, the board can continue to have the effects of purifying, antibacterial and mildew-proofing under the action of light. The manufacturing method disclosed by the present invention improves the environmental quality and function of the fiberboard and meets the needs of high-quality life. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with the embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.

[0039] Example

[0040] 1. Preparation process of environmentally friendly glue for E0 grade poplar fiberboard:

[0041] Feeding amount:

[0042] Formaldehyde: F1=9500kg, F2=1800kg;

[0043] Urea: U1 = 3300 kg, U2 = 1400 kg, U3 = 4350 kg;

[0044] Melamine: M = 2700 kg;

[0045] 1. Add F1, add caustic soda solution (25%), and adjust pH = 8.5-9.0;

[0046] 2. Add U1, start the mixer, heat to 85°C over 30-40 minutes with steam, keep warm for 15 minutes, and control the pH at 6.5-7.5;

[0047] 3. Slowly add formic acid to adjust the pH to 4.5-4.7, and react at 88-89°C until white mist appears when the reaction solution is dropped into ice water;

[0048] 4. Add caustic soda solution, adjust the pH of the reaction solution to 6.0-6.5, and add U2;

[0049] 5. Raise the temperature to 85°C, keep warm for 10 minutes, add caustic soda solution to adjust pH to 9.0-9.3, and add M;

[0050] 6. Add F2, raise the temperature to 88-92℃, and keep the temperature at 90℃ for 45 minutes; during the 45-minute temperature keeping, the pH value should always be kept above 8.3. If the pH value drops, add caustic soda solution to adjust it;

[0051] 7. After constant temperature is finished, cool quickly with cooling water, add U3 at 80℃, cool to 35℃, adjust pH=7.6-8.0, and discharge the glue.

[0052] 2. Preparation method of deodorant

[0053] 1. Weigh plant extracts: 8 parts of tea polyphenols extract, 6 parts of rosemary extract, 6 parts of licorice extract, and 1 part of citric acid; weigh 32 parts of emulsifier Tween 20T-20, 10 parts of fatty alcohol polyoxyethylene ether AEO-9, and 18 parts of Span-80, add them into a container, and stir to make them uniform;

[0054] 2. Dissolve 25 parts of hydroxypropyl-β-cyclodextrin in 225 parts of deionized water to prepare an aqueous solution with a concentration of about 10%, then slowly pour the hydroxypropyl-β-cyclodextrin solution into the mixture in step 1 along the wall, and stir to make the solution system uniform;

[0055] 3. Use 0.1 mol / L sodium hydroxide solution to adjust the pH to 7-8;

[0056] 4. Stir at room temperature for 4 hours. After the system is stable, add 25 parts of nano titanium dioxide and continue stirring at room temperature to obtain a translucent to white emulsion.

[0057] 3. Manufacturing method of low odor poplar fiberboard

[0058] The poplar is chipped, and an antibacterial and antifungal agent is added during the chipping process. The amount of the antibacterial and antifungal agent added is 0.1-1% relative to the absolute dry wood chips. In order to apply the agent fully and evenly, the antifungal agent is diluted with water at a ratio of 1:10;

[0059] Poplar wood chips are stored in the wood chip warehouse for 1-2 months before use. The odor of the wood chips will be significantly reduced after storage. Due to the addition of antibacterial and mildew-proof agents, odor caused by microbial mildew during storage can be avoided.

[0060] The wood chips are screened and then washed to remove impurities such as sand. The wood chips are pre-cooked and then enter the cooking process. The pre-cooking temperature is 90°C, the cooking temperature is 165°C, and the cooking time is 2.5 minutes.

[0061] The cooked wood chips enter the mill for fiber separation, and 58# fully refined paraffin is added to the mill, with the amount of paraffin added being 6kg / m 3 , add curing agent, environmentally friendly glue and deodorant to the spray pipe, among which, the amount of curing agent added is 2.5kg / m 3 , the application amount of environmentally friendly glue is 200kg / m 3 , the amount of deodorant added is 2kg / m 3 The deodorant can be applied alone or mixed with the environmentally friendly glue in proportion and then applied together;

[0062] The fiber after sizing is dried by flue gas and then enters the fiber silo. The inlet temperature of the flue gas drying is 180℃ and the outlet temperature is 80℃. The moisture content of the fiber after drying is controlled at 9-12%;

[0063] The fibers in the silo are laid by the laying machine and pre-pressed after laying. The pre-pressed fiber sheet enters the press for hot pressing. The hot pressing temperatures are 228, 218, 205, 196, and 180℃, and the hot pressing factor is controlled at 7.6-7.8s / mm.

[0064] The low-odor boards coming out of the press are cooled by the board turning machine and then stacked in a separate warehouse to avoid interference with boards with other odors;

[0065] After 48 hours of storage, the boards are sanded and sorted for storage.

[0066] The 10mm E0 grade poplar fiberboard prepared by the above steps was tested according to GB / T11718-2019, LY / T3236-2020, HJ571-2010, and LY / T2230-2013 standards, and the results are as follows:

[0067] Performance Indicators <![CDATA[10mm E0 grade poplar fiberboard]]> <![CDATA[Density kg / m 3 > 845 Surface bonding strength MPa 1.9 Board moisture content% 5.8 Internal bonding strength MPa 1.8 Static bending strength MPa 52 Water absorption thickness expansion rate % 5.1 Formaldehyde emission mg / 100g 4.4 Odor level Level 1.8 <![CDATA[TVOC mg / (m 2 ·h)72h]]> 0.20 Mildew resistance level Level 1

[0068] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for manufacturing an E0-grade poplar low-odor fiberboard, comprising: Poplar peeling → chipping, adding antibacterial and mildew-proofing agents → storage for 1 to 2 months → wood chip screening → water washing → cooking → fiber separation → glue application, including applying deodorant, environmentally friendly adhesive, waterproofing agent, curing agent → drying and sorting → paving and forming → pre-pressing → hot pressing → cooling → sanding → spraying sealant → inspection and grading → packaging and storage, which is characterized by: In the step of adding an antibacterial and antifungal agent to the chips, 0.1 to 1% of the antibacterial and antifungal agent is added to the poplar chips relative to the mass of the absolute dry wood chips; In the cooking process, the pre-cooking temperature is 85-90°C, the cooking temperature is 160-170°C, and the cooking time is 2-2.5 minutes; The adhesive preparation includes applying a deodorant, an environmentally friendly adhesive, a waterproofing agent, and a curing agent. The amount of the deodorant added is 1 to 3 kg / m 3 , the application amount of environmentally friendly adhesive is 175~220kg / m 3 , the amount of waterproofing agent added is 4 to 8 kg / m 3 , the amount of curing agent added is 2~4kg / m 3 , each component is applied relative to the volume of the wood fiber.

2. The method for manufacturing the E0-grade poplar low-odor fiberboard according to claim 1, characterized in that: In the step of adding the antibacterial and mildew-proofing agent to the chips, 0.5% of the antibacterial and mildew-proofing agent is added to the poplar chips relative to the mass of the absolutely dry wood chips.

3. The method for manufacturing the E0-grade poplar low-odor fiberboard according to claim 1, characterized in that: The deodorant is applied to the poplar wood fiber alone, or is mixed with the environmentally friendly adhesive and then applied to the poplar wood fiber at the same time.

4. The method for manufacturing the E0-grade poplar low-odor fiberboard according to claim 1, characterized in that: The main component of the deodorant is nano titanium dioxide.

5. The method for manufacturing the E0-grade poplar low-odor fiberboard according to claim 1, characterized in that: The waterproofing agent is No. 58 fully refined paraffin.

6. The method for manufacturing the E0-grade poplar low-odor fiberboard according to claim 1, characterized in that: The curing agent is a composite curing agent, which is a mixture of phosphoric acid and ammonium sulfate in a molar ratio of 1:

1. The concentration of the aqueous solution after the two are mixed is 20-40%, and the pH of the aqueous solution is 4-5.

7. The method for manufacturing the E0-grade poplar low-odor fiberboard according to claim 1, characterized in that: The adhesive preparation includes applying deodorant, environmentally friendly adhesive, waterproof agent and curing agent. The amount of deodorant added is 2kg / m 3 , the application amount of environmentally friendly adhesive is 200kg / m 3 , the amount of waterproofing agent added is 6kg / m 3 , the amount of curing agent added is 3kg / m 3 , each component is applied relative to the volume of the wood fiber.

8. The method for manufacturing the E0-grade poplar low-odor fiberboard according to claim 1, characterized in that: In the drying and sorting process, the inlet temperature of the drying temperature is 160-180°C, and the outlet temperature is 80-90°C.

9. The method for manufacturing the E0-grade poplar low-odor fiberboard according to claim 1, characterized in that: In the hot pressing process, the hot pressing temperature is set at 170-235° C., five temperature zones are used, the hot pressing pressure is 0-4 MPa, the hot pressing factor is 7.0-8.0 s / mm, and the maximum pressure is 3 MPa.

10. The E0-grade poplar low-odor fiberboard manufactured according to any one of claims 1 to 9, characterized in that: In addition to meeting all the physical and chemical properties of ordinary fiberboard GB / T11718, the E0-grade poplar low-odor fiberboard also meets the odor level ≤ Level 2 in LY / T3236-2020 "Odor Classification and Evaluation Methods for Artificial Boards and Their Products".

Citation Information

Patent Citations

  • Preparation method for all-poplar-wood high-density floor base material

    CN105563603A

  • Preparation method of formaldehyde-removing composite material

    CN106139895A

  • Preparation method of self-fragrance natural antibacterial and deodorizing fiber and application thereof

    CN106637498A

  • Manufacturing method of density fiberboard for E0-level electronic circuit base plate

    CN110744670A

  • Preparation method of bamboo-wood composite material and bamboo-wood composite material

    CN111452178A

Cited By

  • Preparation method of floor base material with deodorization and antibacterial functions

    CN121083753A

  • Manufacturing method of low-odor shaving board

    CN121200172A